Comparative analyses on a batch-type heat pump dryer using low GWP refrigerants - Singh A.; Sarkar J.; Sahoo R.R. (My University, 2025)
The simulation of batch type open cycle heat pump dryer has been performed to study the system performances and food quality using promising low GWP refrigerants (R290, R600a, R32, R152a and R1234yf) as a substitute of R134a for carrot and banana drying. The experimentation with heat pump dryer test facility using R134a has been performed for model validation. Effects of drying time and material moisture content on the coefficient of performance, moisture extraction rate, specific moisture extraction rate, specific energy consumption, drying efficiency, exergy destruction, exergy efficiency and product water activity have been investigated. Results show that moisture extraction rate is maximum for R32, specific moisture extraction rate is maximum for R152a, specific energy consumption is minimum for R152a, drying efficiency is maximum for R152a (average value is 29.74%) and exergy destruction is minimum for R152a for the same air inlet velocity of 2 m/s, respectively. The present study reveals that R152a may be a potential option for heat pump dryer by considering performances, environmental safety (low GWP) and personal safety (low flammability). © 2019 Institution of Chemical Engineers